Leaning Into the Liminal: A Guide for Counselors and Companions (2024). Edited by Timothy L. Carson. ⁠The Liminality Press. ISBN: ‏9798989164004 - Willa Thāniyā Reid (Psychotherapy and Counselling Journal of Australia)
Liminality is a concept that straddles various domains of thought and practice. In the context of human suffering the concept has much to offer clinical practitioners who work with clients undergoing significant life changes. In _Leaning Into the Liminal: A Guide for Counselors and Companions_ (2024a), editor Dr. Timothy L. Carson facilitates a range of voices exploring the meanings and uses of liminality. Carson is a pastor who completed his doctoral research on liminality and now heads the Liminality Project at the University of Missouri. The concept of liminality is treated in the text as a description of how people move through the disorientating passage from what is known, through unknowing, and into the new. Individuals traverse such passages when they experience key changes in life. Protocols for supporting this movement are a valuable part of the discussions in this book. The book is organised into sections dealing with liminality in clinical practice, recovery from war (including in Ukraine), spiritual direction, and dying. This exploration will be helpful to counsellors, psychotherapists, and practitioners who are unfamiliar with this liminal perspective on human experience. Some of the contributions to the book are tender and intimate in a way that supports a deepening engagement with these essential life transitions.